Engineering anodes for rechargeable aqueous aluminum-ion batteries - Jia, Beier (Nanyang Technological University, 2025)
The increasing utilization of renewable energy sources, including wind and solar power, has created new demands for safe, low-cost, and reliable electrochemical energy storage (EES). Existing EES systems, primarily based on lithium (Li)-ion batteries, face challenges, including the scarcity of Li reserves and safety concerns. Consequently, the development of "beyond Li" batteries has become a research hotspot. Among these, rechargeable aqueous aluminum-ion batteries (AAIBs) have garnered significant attention because of their notable advantages. These include the intrinsic safety provided by aqueous electrolytes, the abundance of aluminum (Al) resources (constituting 8.23 wt% of the Earth's crust), the low cost of Al metal, and its well-established industry. Specifically, employing Al metal as the battery anode theoretically offers a substantial gravimetric capacity of 2980 mAh g−1 and a volumetric capacity of 8046 mAh cm−3. However, the development of Al metal anodes in aqueous electrolytes is hindered by several issues, including surface passivating films that obstruct charge/ion transport, the highly negative deposition potential of Al ions, which induces hydrogen evolution reaction (HER), poor reversibility of Al stripping/plating (ASP), low battery voltage plateaus, and poor cycle stability, all of which diminish the attractiveness of aqueous aluminum metal batteries (AAMBs). This thesis aims to alleviate these key challenges of Al anodes through anode engineering strategies, such as amorphization, composite heterometallic structures, and coating with transition metal disulfides (TMDs). These approaches aim to alleviate passivation, enhance the ASP reversibility, and suppress side reactions like HER and corrosion, thereby improving the voltage plateau, specific capacity, and cycle stability of AAMBs.